2017
DOI: 10.1111/1751-7915.12761
|View full text |Cite
|
Sign up to set email alerts
|

An ArsR/SmtB family member regulates arsenic resistance genes unusually arranged in Thermus thermophilus HB27

Abstract: SummaryArsenic resistance is commonly clustered in ars operons in bacteria; main ars operon components encode an arsenate reductase, a membrane extrusion protein, and an As‐sensitive transcription factor. In the As‐resistant thermophile Thermus thermophilus HB27, genes encoding homologues of these proteins are interspersed in the chromosome. In this article, we show that two adjacent genes, TtsmtB, encoding an ArsR/SmtB transcriptional repressor and, TTC0354, encoding a Zn2+/Cd2+‐dependent membrane ATPase are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 46 publications
3
56
0
1
Order By: Relevance
“…For instance, gram-positive and gram-negative bacteria possess arsenic resistance systems encoded by operons carried either on plasmids or on the chromosome. Genetic determinants are usually the three genes arsR, arsB, and arsC [18,19], among which arsR encodes a trans-acting repressor of the ArsR/SmtB family involved in transcriptional regulation [20][21][22], arsB encodes an As(III) efflux transporter (ArsB/Acr3) [23], and arsC encodes a cytoplasmic arsenate reductase that converts As(V) to As(III), the latter extruded outside the cell [24][25][26]. Other organisms benefit of additional proteins that improve the arsenic resistance, such as the arsenite methyltransferases [27].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, gram-positive and gram-negative bacteria possess arsenic resistance systems encoded by operons carried either on plasmids or on the chromosome. Genetic determinants are usually the three genes arsR, arsB, and arsC [18,19], among which arsR encodes a trans-acting repressor of the ArsR/SmtB family involved in transcriptional regulation [20][21][22], arsB encodes an As(III) efflux transporter (ArsB/Acr3) [23], and arsC encodes a cytoplasmic arsenate reductase that converts As(V) to As(III), the latter extruded outside the cell [24][25][26]. Other organisms benefit of additional proteins that improve the arsenic resistance, such as the arsenite methyltransferases [27].…”
Section: Introductionmentioning
confidence: 99%
“…Thermus thermophilus HB27 is a thermophilic aerobic Gram-negative bacterium capable of growing in the presence of arsenic concentrations that are lethal for other microorganisms [ 21 ]. In recent studies we demonstrated that the arsenic resistance system is not clustered in a single ars operon as in other organisms, but the genes are spread in the genome: TTC1502 encoding a cytoplasmic arsenate reductase ( Tt ArsC) able to reduce arsenate to arsenite, TTC0354 , encoding a P 1B -type membrane ATPase responsible for the efflux (herein named Tt ArsX) and TTC0353 encoding a repressor ( Tt SmtB) sensitive to both As(V) and As(III) [ 22 24 ]. Tt SmtB is a member of the ArsR/SmtB family, sharing 50% identity with the well characterized SmtB of Synechococcus PCC7942 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both in Gram-positive and Gram-negative bacteria the arsenic resistance system is composed by operons of 3-5 genes carried on plasmids or chromosomes; the two most common contain either five genes (arsRDABC), as in the plasmid R773 of the Escherichia coli, or three genes (arsRBC), as in the plasmid pI258 of Staphylococcus aureus [36,37]. The arsR gene encodes a trans-acting repressor of the ArsR/SmtB family involved in transcriptional regulation [30], arsB encodes an As(III) efflux transporter [38], and arsC encodes a cytoplasmic arsenate reductase that converts As(V) to As(III), which is extruded outside the cell [39]. Where present, ArsD is a metallochaperone that transfers trivalent metalloids to ArsA, the arsenite-stimulated efflux ATPase [31].…”
Section: Metal Resistance Mechanismsmentioning
confidence: 99%
“…These systems are generally finely regulated by specific transcription factors. As an example, the transcription of the arsenic resistance system of T. thermophilus HB27 is regulated by TtSmtB, a protein belonging to the ArsR/SmtB family which acts as the As(V) and As(III) intracellular sensor [30]. In the absence of metal ions, the protein binds to regulatory regions upstream of TTC1502, encoding TtArsC, and TTC0354, encoding the efflux membrane protein TtArsX, (a P 1B -type ATPase, see above).…”
Section: Enzymatic Reduction Of Metal Ions: Metal Reductasesmentioning
confidence: 99%